Trimethoprim-Sulfamethoxazole-Induced Hyperkalemia in a Patient with Normal Renal Function. (13th December 2012) - Nickels, L. Connor; Jones, Christine; Stead, Latha Ganti
Abstract : The authors present a case of Trimethoprim-sulfamethoxazole-induced hyperkalemia in a patient with normal renal function. While toxicity of this drug has been reported in patients with renal insufficiency, this case highlights the toxicity associated with normal kidney function. Due to its popularity in the medical field and to the largely unrecognized effect of hyperkalemia, it is important to consider such adverse effects when prescribing TMX-SMX. One must be reminded of the possibility of the development of life-threatening hyperkalemia in relatively healthy patients.